Availability and accessibility of liability and excess insurance for public transit and private coach operators. - Burkert, Jack.; Ellis, Elizabeth; Knapp, Sue.; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board; KFH Group, Inc.; Cambridge Systematics (Washington, DC Transportation Research Board, 2005)
"This digest provides the results of NCHRP Project 20-65(3) ... This digest was prepared by Jack Burkert, Consultant, and Elizabeth Ellis and Sue Knapp of KFH Group, Inc., in association with Cambridge Systematics"--P. [1].
Caption title.
"March 2005."
Includes bibliographical references (p. 33-35).
Also available online via the Transportation Research Board web site (www.trb.org).
Keywords: Local transit -- Insurance -- United States; Bus lines -- Insurance -- United States